2022
DOI: 10.1093/cid/ciac974
|View full text |Cite
|
Sign up to set email alerts
|

Same-Day Treatment Following Point-of-Care Sexually Transmitted Infection Testing in Different Healthcare Settings in South Africa

Abstract: We would like to congratulate Asare et al [1] on their analysis of the outcomes of point-of-care (POC) testing for sexually transmitted infections (STIs) among women in South Africa during an HIV vaccine trial. They found that, in one clinic, 92% of women with a positive test result for

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 2 publications
0
1
0
Order By: Relevance
“…Research studies using in-facility Xpert assay testing have shown major benefits of STI point-of-care diagnostic testing on the time to treatment in syndromic manage ment settings. [23][24][25][26] Another recent development is the Visby Medical Sexual Health Test; a rapid singleuse molecular point-of-care test for multiple STIs. 27 Despite high test performance of these assays, molecular test technology is likely to remain too expensive for widespread use in lower-income settings.…”
Section: Discussionmentioning
confidence: 99%
“…Research studies using in-facility Xpert assay testing have shown major benefits of STI point-of-care diagnostic testing on the time to treatment in syndromic manage ment settings. [23][24][25][26] Another recent development is the Visby Medical Sexual Health Test; a rapid singleuse molecular point-of-care test for multiple STIs. 27 Despite high test performance of these assays, molecular test technology is likely to remain too expensive for widespread use in lower-income settings.…”
Section: Discussionmentioning
confidence: 99%
“…Participants were recruited between April and December 2023 from three southern African sites: 1) Cape Town, SA; 2) East London, SA; and 3) Gaborone, Botswana, with antenatal care HIV prevalence estimated from previous studies at 20.3%, 29% and 17%, respectively [52][53][54]. Collaborating healthcare facilities in East London were de ned to cater to peri-urban and rural areas, whereas Cape Town and Gaborone were predominantly characterized as urban.…”
Section: Study Population and Samplingmentioning
confidence: 99%